Women's Experiences of Looking and Being Looked At - Green, Emma (Auckland University of Technology, 2020)
This thesis seeks to better understand women’s lived experiences of looking and being looked at. Unstructured interviews with 14 women were used to gather data. A hermeneutic-phenomenological methodology provided the framework. This approach relied on the hermeneutic spiral to unfold the back and forth between parts and whole, allowing the phenomenon to emerge. The study draws on the thinking of Gadamer [1900-2002], recognising that all attempts at understanding are interpretations and that all interpretations are from a particular horizon—revealing the prejudices of the one who is interpreting. Poetical thinking, and the use of poetry to analyse and (re)present findings, offers a way in to the lived experience; distilling and disclosing meaning and facilitating deeper understandings. The research provides significant insight into women’s lived experiences of looking—at others and self—and being looked at. This is important since there is currently little research that offers an account of the meanings women make of such experiences. Women described largely negative experiences of looking at self and being looked at, and how looking at others stirred feelings of disappointment with their own bodies. Inherent to women’s experiences is the power of looking and being looked at to shape, and sometimes disturb, the self. Yearning, comparing and feeling exposed are revealed as essential meanings in the lived experience of looking and being looked at. Yearning and comparing mean women feel disappointed and disappointing, as well as longing for that which is looked at. Feelings of being exposed disclose the vulnerability inherent in women’s experience, as well as illuminating looking and being looked at as foundational to being itself. The meanings revealed in the research prompt questions and offer insights useful for psychotherapy practice. The use of poetry to crystallise the meanings of the phenomenon also reveals the potential for the use of poetic inquiry in research and psychotherapy practice to surface and distil meaning, and promote deeper understandings of a phenomenon. Furthermore, the method will be of interest to those studying psychotherapy as a ‘way in’ to the clinical material, affording opportunities for more profound reflection and engagement with the work.
Keywords: Hermeneutics; Hermeneutic phenomenology; Poetic inquiry; Lived experience; Looking; Looked at; Psychotherapy; Women's experience